Optimizing MRI for Imaging Peripheral Arthritis - Hodgson, Richard J.; O'Connor, Philip J.; Ridgway, John P. (Seminars in Musculoskeletal Radiology, 2012)
MRI is increasingly used for the assessment of both inflammatory arthritis and osteoarthritis. The wide variety of MRI systems in use ranges from low-field, low-cost extremity units to whole-body high-field 7-T systems, each with different strengths for specific applications. The availability of dedicated radiofrequency phased-array coils allows the rapid acquisition of high-resolution images of one or more peripheral joints. MRI is uniquely flexible in its ability to manipulate image contrast, and individual MR sequences may be combined into protocols to sensitively visualize multiple features of arthritis including synovitis, bone marrow lesions, erosions, cartilage changes, and tendinopathy. Careful choice of the imaging parameters allows images to be generated with optimal quality while minimizing unwanted artifacts. Finally, there are many novel MRI techniques that can quantify disease levels in arthritis in tissues including synovitis and cartilage.
Keywords: MRI; arthritis; techniques